New Oxford Textbook of Psychiatry - Michael G. Gelder , Juan J. López-Ibor Nancy Andreasen (OXFORD UNIVERSITY PRESS, 2007)
Three themes can be discerned in contemporary psychiatry: the growing unity of the subject, the pace of scientific advance, and the growth of practice in the community. We have sought to reflect these themes in the New Oxford Textbook of Psychiatry and to present the state of psychiatry at the start of the new millennium. The book is written for psychiatrists engaged in continuous education and recertification; the previous, shorter, Oxford Textbook of Psychiatry remains available for psychiatrists in training. The book is intended to be suitable also as a work of reference for psychiatrists of all levels of experience, and for other professionals whose work involves them in the problems of psychiatry.